2017
DOI: 10.1007/s13365-017-0516-1
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barre syndrome complicating chikungunya virus infection

Abstract: Chikungunya virus (CHIKV) is a mosquito-borne alphavirus which presents with symptoms of fever, rash, arthralgia, and occasional neurologic disease. While outbreaks have been earlier reported from India and other parts of the world, the recent outbreak in India witnessed more than 1000 cases. Various systemic and rarely neurological complications have been reported with CHIKV. We report two cases of Guillain-Barré syndrome (GBS) with CHIKV. GBS is a rare neurological complication which may occur after subsiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 11 publications
2
25
1
3
Order By: Relevance
“…The first neurological alterations found in GBS cases associated with arboviruses referred to movement and walking, which is in accordance with previous findings [25,33,40]. A study carried out in France in 2009 reported two GBS cases after chikungunya; the patients were a 48 and 51-year-old women, presenting progressive movement weakness, lack of tendon reflex, and sensory disorder [25].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The first neurological alterations found in GBS cases associated with arboviruses referred to movement and walking, which is in accordance with previous findings [25,33,40]. A study carried out in France in 2009 reported two GBS cases after chikungunya; the patients were a 48 and 51-year-old women, presenting progressive movement weakness, lack of tendon reflex, and sensory disorder [25].…”
Section: Discussionsupporting
confidence: 88%
“…There is a smaller number of GBS case reports after chikungunya compared to those reported for dengue and Zika virus [33]. However, 15 confirmed/ probable post-chikungunya GBS cases were recorded in this research, totaling 35.0% of the notified cases.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Clinically, chikungunya‐associated GBS resembles GBS associated with other infections such as Campylobacter jejuni , presenting with symmetrical, bilateral flaccid weakness, often with paraesthesia and/or cranial nerve palsy . The 4 reports in the literature detailing the time interval between chikungunya infection and onset of neurological features describe a prodrome of 3 to 17 days, compatible with a parainfectious or postinfectious syndrome (Table ) …”
Section: Neurological Manifestationsmentioning
confidence: 99%
“…A second major outbreak in French Polynesia from October 2013 to April 2014, during which approximately 31,000 persons were infected, 65 provided the first indication that Zika virus could cause neurologic disease. 66 A major uptick in the incidence of Guillain-Barré syndrome, which has been described with other arbovirus infections, 67,68 temporally coincided with the French Polynesia outbreak (►Fig. 2).…”
Section: Guillain-barré Syndrome Associated With Zika Virusmentioning
confidence: 99%